Germline mutations of KIT in gastrointestinal stromal tumor (GIST) and mastocytosis. Issue 1 (December 2016) - Ke, Hengning; Kazi, Julhash; Zhao, Hui; Sun, Jianmin
Abstract Somatic mutations of KIT are frequently found in mastocytosis and gastrointestinal stromal tumor (GIST), while germline mutations of KIT are rare, and only found in few cases of familial GIST and mastocytosis. Although ligand-independent activation is the common feature of KIT mutations, the phenotypes mediated by various germline KIT mutations are different. Germline KIT mutations affect different tissues such as interstitial cells of Cajal (ICC), mast cells or melanocytes, and thereby lead to GIST, mastocytosis, or abnormal pigmentation. In this review, we summarize germline KIT mutations in familial mastocytosis and GIST and discuss the possible cellular context dependent transforming activity of KIT mutations.